Methotrexate and a spleen tyrosine kinase inhibitor cooperate to inhibit responses to peripheral blood B cells in rheumatoid arthritis. Issue 2 (15th December 2013) - Coffey, Greg; Betz, Andreas; Graf, Jonathan; Stephens, Gillian; Hua Lin, Pei; Imboden, John; Sinha, Uma
Abstract Background Selective disruption of the spleen tyrosine kinase (Syk) represents a novel strategy to control B‐cell functional responses by inhibition of B‐cell antigen receptor (BCR) signaling. PRT062607 (P505‐15) is a highly selective small molecule Syk inhibitor that potently suppresses B‐cell function in human and rodent blood, and reduces inflammation in rodent models of rheumatoid arthritis (RA). Aims In this study, we sought to determine the potency of Syk inhibition by PRT062607 in whole blood from RA patients, and elucidate covariates that affect the potency of immune‐regulation by this compound. Materials and Methods Whole blood was collected from 30 patients diagnosed with RA as part of a single‐center outpatient study. Disease severity, serum protein markers of inflammation, and co‐medications were related to each other, and to PRT062607 activity in ex vivo Syk‐mediated immune function assays. Results We report here that PRT062607 exhibited greater potency in suppressing BCR mediated B‐cell functional responses in whole blood from RA patients who received stable methotrexate (MTX) therapy. We demonstrate that the B‐cell functional response to BCR ligation is influenced by cytokines and JAK/STAT signaling. Discussion MTX is a known cytokine modulating agent, and this mechanism may act in concert with PRT062607 to control B‐cell function. Conclusion These data have important implications for the co‐administration of Syk inhibitors and MTX for the treatment of RA.